Reduced skeletal muscle satellite cell number alters muscle morphology after chronic stretch but allows limited serial sarcomere addition. Issue 3 (28th November 2016) - Kinney, Matthew C.; Dayanidhi, Sudarshan; Dykstra, Peter B.; McCarthy, John J.; Peterson, Charlotte A.; Lieber, Richard L.
ABSTRACT: Introduction : Muscles add sarcomeres in response to stretch, presumably to maintain optimal sarcomere length. Clinical evidence from patients with cerebral palsy, who have both decreased serial sarcomere number and reduced satellite cells (SCs), suggests a hypothesis that SCs may be involved in sarcomere addition. Methods : A transgenic Pax7‐DTA mouse model underwent conditional SC depletion, and their soleii were then stretch‐immobilized to assess the capacity for sarcomere addition. Muscle architecture, morphology, and extracellular matrix (ECM) changes were also evaluated. Results : Mice in the SC‐reduced group achieved normal serial sarcomere addition in response to stretch. However, muscle fiber cross‐sectional area was significantly smaller and was associated with hypertrophic ECM changes, consistent with fibrosis. Conclusions : While a reduced SC population does not hinder serial sarcomere addition, SCs play a role in muscle adaptation to chronic stretch that involves maintenance of both fiber cross‐sectional area and ECM structure. Muscle Nerve 55 : 384–392, 2017